Macro-/Microstructural Features and Temperature Distribution of Pure Aluminum 1070 in Novel Thin Slab Continuous Casting Process - Qijia Mao; Fuan Hua; Zhuohuang Wu; Shuai Zhao; Guanglin Jia; Guo Yuan; Guodong Wang (Crystals)
This study introduces a novel vertical bending continuous casting technology for producing thin slabs of pure aluminum and aluminum alloys, offering significant advancements over traditional vertical casting methods. The newly designed equipment and optimized process parameters enable the continuous casting of pure aluminum 1070 at a speed of 1.2 m/min, surpassing the casting speed of conventional direct-chill casting. Comprehensive investigations of the macrostructure and microstructure of the cast pure aluminum 1070 reveal a refined equiaxed crystal structure with an average grain size of 98 μm, significantly smaller than that obtained through conventional casting processes. This refinement in grain size is expected to enhance the material’s mechanical properties and processing capabilities. Additionally, simulations of the temperature distribution and solidification structure provide insights into the formation of a “U”-shaped sump and liquidus isotherms, which are crucial for understanding the solidification dynamics of the material. The refined grain structure and increased casting speed demonstrate substantial potential for advancing aluminum alloy production, especially in applications requiring superior performance and more efficient manufacturing processes.